PROJECT-BASED LEARNING OF THE QURAN IN ISLAMIC EDUCATION MANAGEMENT: AN INNOVATIVE APPROACH IN INTEGRATED ISLAMIC SCHOOLS - Al Husaini, Muhammad; Harahap, Nasrudin; Hidayati Murtafiah, Nurul (Sekolah Tinggi Keguruan dan Pendidikan Syekh Manshur, 2023)
This research investigates the implementation of Project-Based Learning of the Qur'an (PBL of the Qur'an) as an innovative approach in Islamic education management in integrated Islamic schools. This approach focuses on deepening the understanding of the Qur'an and integrating Islamic values into the daily lives of students. The study analyzes the benefits and challenges encountered during the implementation of PBL of the Qur'an. The research findings reveal that this approach offers significant benefits, including a deep understanding of the Qur'an, the development of practical skills, the integration of Islamic values into real-life actions, student engagement, and the involvement of parents and the community in the educational process. However, its implementation also faces challenges, such as adequate resource preparation, the evaluation of outcomes reflecting Qur'anic understanding, teacher commitment, and integration into existing curricula. Recommendations include teacher and staff training, the development of relevant teaching materials, improved evaluation methods, collaboration with parents and the community, and the need for further research in the implementation of PBL of the Qur'an. This research makes a significant contribution to understanding Islamic education management and innovative learning methods to create a relevant Islamic education that aligns with Islamic values in a constantly evolving world.